Five challenges for manual therapies trials with placebo controls: A proposal. (December 2022) - D'Alessandro, Giandomenico; Ruffini, Nuria; Iacopini, Alessio; Annoni, Marco; Kossowsky, Joe; Cerritelli, Francesco
Abstract: Randomised placebo-controlled trials (RCT) are implemented to determine whether a particular therapy is superior to placebo and can thus be considered effective. However, adopting the standard RCT design in contexts other than pharmacological trials, such as manual therapy, may result in systematic biases. These biases may occur due to: the impossibility of traditional "double-blinding" in manual therapy trials; insufficient pre-training of operators delivering the treatment and/or sham therapy; biased recruitment of study participants; the problematic use of subjective and/or objective outcomes; and finally, the presence of phenomena mimicking placebo effects. From the perspective of placebo studies, the purpose of this paper is to discuss and make appropriate recommendations to address these five issues in manual therapy research.